PENGARUH BIAYA KUALITAS TERHADAP PRODUK RUSAK PADA CV. HUTOMO PUTRA NGANJUK - suwandi suwandi (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2016)
In the era of industrialization increasingly competitive, companies are required to participate in the competition. One attempt by the company to be competitive is to improve the quality of their products. If the quality of the product increases, will reduce the occurrence of defective products resulting costs continue to decline and ultimately increase profits. Costs incurred to improve the quality of the so-called cost of quality. According to Hansen and Mowen quality costs consist of the costs of prevention and appraisal costs have a negative effect on defective products, while Feigenbaum said the increase in costs resulting decline in the prevention of disability, which in turn has a positive effect on costs due to lower disability ratings mean lower demand for aktivitas- inspection and testing activities are routine. CV. Hutomo Putra Nganjuk has done quality improvement program but has yet to do grouping and reporting the cost of quality, so that the management can not control the expenditure cost of optimal quality. Referring to the above description, the issue of concern is how much influence the quality costs consist of the costs of prevention and appraisal costs against defective products either simultaneously or partially on the CV. Hutomo Putra Nganjuk. Object of this study is the CV. Hutomo Son Nganjuk. The variables studied were the cost of quality (prevention costs and appraisal costs) and defective products. Data taken with the method of documentation and interviews. Data were analyzed by descriptive and inferential. The results showed that the simultaneous prevention costs and appraisal costs significantly influence the defective product at CV. Hutomo Putra Nganjuk, the calculated F value significant value 4.834 and 0.014 at the significant level of 0.05 and determination coefficient of 0.718, which means the cost of prevention and appraisal costs simultaneously influence the defective product at 71.8%, while the remaining 28.2% defective products is influenced by other factors. Partial cost of prevention and appraisal costs are also significantly influence the defective product. Prevention costs negatively affect the defective product and the cost assessment positive effect on defective products. Based on the results of the study concluded that the costs of prevention, appraisal costs and damaged products fluctuating within reasonable limits, but there are some that go beyond reasonable limits that need the attention of management . It is therefore advised to CV. Hutomo Putra Nganjuk account of costs of prevention and appraisal costs, because the cost of research based prevention can reduce the amount raised if the product is defective, while the assessment fee when unloaded can reduce the number of defective products.